Resilience model based Roy Adaptation Model toward self-care among women living with HIV in Surabaya, Indonesia - Yuanita Wulandari; Nursalam; Ninuk Dian Kurniawati; Mundakir; Farida Umama (Universitas Airlangga, 2026)
Introduction: Women living with HIV face clinical, psychological, and social challenges that can affect self-care. While demographic and disease-related factors have been widely studied, the roles of adaptation and resilience in self-care remain unclear. Objective: To develop and test a resilience model based on the Roy Adaptation Model to explain self-care among women living with HIV in Surabaya, Indonesia. Methods: A cross-sectional study was conducted among 111 women living with HIV recruited through purposive sampling from primary healthcare centers in Surabaya. Eligible participants were women aged ≥18 years receiving antiretroviral therapy for at least three months, able to complete an online questionnaire, and without diagnosed mental disorders or a history of substance abuse treatment. Data were collected using structured questionnaires measuring focal, contextual, and residual stimuli, coping mechanisms, adaptation modes, resilience, and self-care. SEM-PLS with 5,000 bootstrap resamples was used to evaluate the proposed model. Results: The measurement model showed satisfactory reliability and validity (CR = .564–.953; AVE > .50). Contextual (β = .170; P-value<.05) and residual stimuli (β = .492; P-value<.05) significantly influenced coping mechanisms, whereas focal stimuli did not. Coping mechanisms were associated with adaptation modes (β = .624; P-value<.05), which in turn were associated with resilience (β = .669; P-value<.05) and self-care (β = 0.758; P-value<.05). Self-care showed the highest predictive relevance (Q² = .425). Conclusion: Self-care among women living with HIV is closely associated with coping, adaptation, and resilience rather than clinical or demographic factors. Keywords: adaptation; HIV; resilience; self-care; women